Exploring Consumer Behaviour Towards Acceptance Of Quick Response (qr) Code Mobile Payment Systems (mps) In Malaysia: Application Of Technology Of Acceptance Model (tam) - Muhamad Azrin Nazri; Nur Shuhada Kamarudin; Agus Salim; Nor Asiah Omar; Aimi Fadzirul Kamarubahrin (The Malaysian Consumer and Family Economics Associ, 2024)
Indexed by MyCite